2016
DOI: 10.1089/vbz.2015.1841
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Evidence of DifferentRickettsiaSpecies in Villeta, Colombia

Abstract: The aim of this work was to detect and identify Rickettsia species in ticks collected in rural areas of Villeta, Colombia. Tick specimens were collected from domestic animals and walls of houses in five rural villages of Villeta town and from humans in Naranjal village (same town). Moreover, a flea collected from the same area was also processed. DNA was extracted and tested by conventional, semi-nested, and nested PCR reactions targeting rickettsial genes. In the ticks collected from humans from Naranjal vill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
12

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 14 publications
1
19
0
12
Order By: Relevance
“…genotype RF2125 from the Thailand-Myanmar border (Parola et al, 2003), but it has been more recently referred to as ‗Candidatus R. asemboensis', following the description of a similar Rickettsia by Jiang et al (2013) in Asembo, Kenya. Studies have shown that DNA sequences of the gltA and other genes from both rickettsiae are very similar; hence they are probably the same species (Jiang et al, 2013;Oteo et al, 2014;Faccini-Martínez et al, 2016). At study sites, infection rate with this Rickettsia was much higher in pools of C. felis, but they were also detected in P. simulans, which commonly co-infest dogs in these areas (Troyo et al, 2012b).…”
Section: Discussionmentioning
confidence: 82%
“…genotype RF2125 from the Thailand-Myanmar border (Parola et al, 2003), but it has been more recently referred to as ‗Candidatus R. asemboensis', following the description of a similar Rickettsia by Jiang et al (2013) in Asembo, Kenya. Studies have shown that DNA sequences of the gltA and other genes from both rickettsiae are very similar; hence they are probably the same species (Jiang et al, 2013;Oteo et al, 2014;Faccini-Martínez et al, 2016). At study sites, infection rate with this Rickettsia was much higher in pools of C. felis, but they were also detected in P. simulans, which commonly co-infest dogs in these areas (Troyo et al, 2012b).…”
Section: Discussionmentioning
confidence: 82%
“…En Brasil se le ha descrito infectando garrapatas R. sanguineus, y ha sido denominada Rickettsia asembonensis cepa KX196267 (16) , relacionada con pulgas C. felis infectadas. Existen reportes de resultados PCR positivos para los genes gltA, ompB y 16S rRNA en pulgas en Colombia, donde las secuencias presentan alta identidad (98,5%, 97,4% y 99,2%, respectivamente para cada gen) con R. felis, y demuestran 99.7% y 100% de identidad con gltA y ompB de Candidatus Rickettsia asemboensis (17) . Por otro lado, alta homología de secuencias de C. felis con Ca.…”
Section: Resultsunclassified
“…Both transstadial and transovarial transmissions occur in A. americanum ticks, and filial infection rates range between 30 and 100 % depending on the level of rickettsiae in ovarial tissues (Burgdorfer et al , 1981). Other tick species in which ‘ Rickettsia amblyommatis ’ has been detected include Amblyomma longirostre in Brazil (Labruna et al , 2004), Amblyomma neumannii and Amblyomma hadanii in Argentina (Labruna et al , 2007; Mastropaolo et al , 2016), Amblyomma cajennense in Mexico, Costa Rica and Colombia (Faccini-Martínez et al , 2016; Hun et al , 2011; Medina et al , 2007), Amblyomma mixtum and Haemaphysalis juxtakochi in Panama (Castro et al , 2015), Amblyomma coelebs in French Guyana (Parola et al , 2007) and Dermacentor variabilis in the USA (Moncayo et al , 2010). In this context, ‘ Rickettsia amblyommatis ’ likely represents the most prevalent and widely distributed SFG rickettsial species in the Americas.…”
mentioning
confidence: 99%